To find out how much money Jaden will earn for 4 lawn-mowing jobs and 6 pulling-weeds jobs, we substitute L = 4 and W = 6 into the expression 25L + 20W:
25(4) + 20(6)
= 100 + 120
= 220
Therefore, Jaden will earn $220 for 4 lawn-mowing jobs and 6 pulling-weeds jobs.
jaden has a part-time job working for a landscaping company. he earns $25 for each lawn-mowing job,L, and $20 for each pulling-weeds job, W. this can be modeled by 25L + 20W. evaluate for L = 4 and w = 6 to find how much money jaden will earn for 4 lawn-mowing jobs and 6 pulling-weeds jobs.
9 answers
alicia works for thomas edison electrical company. she earns $100 for going to a customer's house and $65 per hour, h, for the job. this modelded by 65h + 100. evaluate for h = 3 to find how much alicia will earn for a job that takes 3 hours.
To find out how much Alicia will earn for a job that takes 3 hours, we substitute h = 3 into the expression 65h + 100:
65(3) + 100
= 195 + 100
= 295
Therefore, Alicia will earn $295 for a job that takes 3 hours.
65(3) + 100
= 195 + 100
= 295
Therefore, Alicia will earn $295 for a job that takes 3 hours.
gabrielle wants to put a border around her garden. it costs $1.50 per yard for the materials. use 1.50(2l + 2w), where l is the length and w is the width of her garden, to find the cost for a garden that has a length of 4 yards and a width of 3 yards.
To find the cost for a garden that has a length of 4 yards and a width of 3 yards, we substitute l = 4 and w = 3 into the expression 1.50(2l + 2w):
1.50(2(4) + 2(3))
= 1.50(8 + 6)
= 1.50(14)
= 21
Therefore, the cost for a garden with a length of 4 yards and a width of 3 yards will be $21.
1.50(2(4) + 2(3))
= 1.50(8 + 6)
= 1.50(14)
= 21
Therefore, the cost for a garden with a length of 4 yards and a width of 3 yards will be $21.
simplify 9/11z - 4/11z.
To simplify the expression 9/11z - 4/11z, we can combine the like terms:
(9/11z) - (4/11z) = (9 - 4) / 11z = 5/11z
Therefore, the simplified expression is 5/11z.
(9/11z) - (4/11z) = (9 - 4) / 11z = 5/11z
Therefore, the simplified expression is 5/11z.
simplify 3/10x + 1/6y + 3/10x + 3/6y. be sure to reduce any fractions to the lowest terms.
To simplify the expression 3/10x + 1/6y + 3/10x + 3/6y, we can combine the like terms:
First, let's group the terms with respect to x and y:
(3/10x + 3/10x) + (1/6y + 3/6y)
Simplifying within each group:
(6/10x) + (4/6y)
Now, let's find a common denominator for the x terms and y terms, which is 10:
(12/20x) + (20/30y)
Simplifying further by reducing the fractions to lowest terms:
(3/5x) + (2/3y)
Therefore, the simplified expression is (3/5x) + (2/3y).
First, let's group the terms with respect to x and y:
(3/10x + 3/10x) + (1/6y + 3/6y)
Simplifying within each group:
(6/10x) + (4/6y)
Now, let's find a common denominator for the x terms and y terms, which is 10:
(12/20x) + (20/30y)
Simplifying further by reducing the fractions to lowest terms:
(3/5x) + (2/3y)
Therefore, the simplified expression is (3/5x) + (2/3y).